PERANAN MIKROORGANISME RHIZOPUS SP. DALAM PEMBUATAN TEMPE - Niea Zahara Phonna; Wan Ridha Rasyida; Nazwa Ramadhona; Zahraa Zalikha; Serly Kusnia Handayani; Anjelita Sinaga; Dwi Khairani; Miftahul Khairani (STKIP Subang, 2026)
Tempeh is a traditional Indonesian fermented food produced through the activity of microorganisms, particularly Rhizopus sp. This study aimed to analyze the role of Rhizopus sp. in the fermentation of soybeans into tempeh. This laboratory experimental research was conducted at the Biology Education Laboratory, Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Sumatera Utara. Fermentation was carried out at a temperature of 28–32°C for 36–48 hours using tempeh starter. The observed parameters included the growth of Rhizopus sp. mycelium and the physical characteristics of tempeh. The results showed that Rhizopus sp. played an important role in producing tempeh with a compact structure, bright white color, homogeneous texture, and characteristic aroma.